Thermal and solutal stratification on MHD nanofluid flow over a porous vertical plate - Kandasamy, Ramasamy; Dharmalingam, R.; Prabhu, K.K. Sivagnana (Elsevier, 2016)
Nanoparticles have the highest credibility to develop the thermal properties compared to conventional particle fluid suspension. Thermal and solutal stratification on heat and mass transfer induced due to a nanofluid over a porous vertical plate is analyzed. The transport equations engaged in the study include the effect of Brownian motion and thermophoresis particle deposition. The nonlinear governing equations and their related boundary conditions are initially looked into dimensionless forms by similarity variables. The resulting equations are solved numerically utilizing the fourth-fifth order Runge–Kutta–Fehlberg method with shooting technique (MAPLE 18). It is investigated that the temperature of the nanofluid and the concentration fraction decelerate with increase in thermal and solutal stratification